The Interplay of Sound Tapestry and Music in the 1992 German Radio Play Adaptation of J.R.R. Tolkien’s The Lord of the Rings - Mildorf, Jarmila (Word, Sound and Music in Radio Drama)

Word, Sound and Music in Radio Drama: An Introduction - Mildorf, Jarmila (Word, Sound and Music in Radio Drama)

Word, Sound and Music in Radio Drama

Materialschonende Verarbeitung von Thermoplasten auf Wave-Schnecken - Schall, Christoph Wilhelm Theodor
Die Extrusion stellt das mengenmäßig dominante Verarbeitungsverfahren für thermoplastische Kunststoffe dar. Daher gibt es starke Bestrebungen in diesem Bereich hin zu einer höheren Wirtschaftlichkeit, welche beispielsweise durch höheren Massedurchsatz bei gleichbleibender Maschinengröße erreicht werden kann, oder aber auch im Hinblick auf eine Kreislaufwirtschaft die Bestrebung hin zu einer materialschonenden Verarbeitung. Beide Bestrebungen erfordern spezielle Schneckenkonzepte. Hierunter fallenWave- Schnecken, welche in beiden Bereichen ein vorteilhaftes Prozessverhalten aufzeigen sollen. Die Auslegung von Wave-Schnecken erfordert jedoch ein stärkeres Verständnis über das geometrieabhängige Prozessverhalten in der Extrusion. Im Rahmen der Dissertation werden zwei Themengebiete angegangen. Das erste Thema ist die Herleitung einer Methode zur Charakterisierung des Abbauverhaltens von Thermoplasten sowie die Nutzung der Charakterisierung als Vorhersagemodell. Das zweite Thema behandelt die Auslegung von Wave-Schnecken basierend auf numerischen Simulationen samt Validierung anhand von sieben Energy-Transfer-Schnecken im Vergleich zu drei konventionellen Schnecken. Hierbei werden unter anderem der Materialabbau, die thermische und die stoffliche Homogenität betrachtet, um ein umfassendes Bild über das Prozessverhalten der Schnecken zu schaffen. Die vorgestellten Untersuchungen dienen schlussendlich zu einer Bestätigung des vorteilhaften Prozessverhaltens von Wave-Schnecken.

Fast model-based calibration of multiple injections for a CI engine using nonlinear optimal control - Moretto, Giordano; Schnell, Nicolas; Frey, Jonathan; Karakaya, Yasin; Amstutz, Alois; Diehl, Moritz; Kasper, Tina; Onder, Christopher (Control Engineering Practice)

Gottes Treue zu Israel (Röm 9–11) - Taschl-Erber, Andrea; Woppowa, Jan (Elementare Bibeltexte)

Corrosion behaviour of self-piercing riveted joints with uncoated rivets in high nitrogen steel - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Production Engineering)

Maghemite nanoparticles synthesis via spray flame synthesis and particle characterization by hole in a tube sampling and scanning mobility particle sizing (HIAT-SMPS) (Applications in Energy and Combustion Science)
In order to standardize spray flame synthesis (SFS) studies, intensive work has been done in recent years on the design of burner types. Thus, in 2019, the so-called SpraySyn1 burner was introduced (SS1), which was subsequently characterized in numerical and experimental studies. Based on this research, a modification of the nozzle design was proposed, which has now been considered in the successor model, SpraySyn2 (SS2). As little is known about the effect of the nozzle adaptation on the particle formation, we operated both burners under identical operating conditions to produce maghemite. The final powder comparison showed that SS2 yielded considerable higher specific surface areas (associated with smaller primary particle sizes), lower polydispersity, and higher phase purity. To obtain further information on the size distributions of aggregates and agglomerates generated by SS2, aerosol samples were extracted by hole in a tube (HIAT) sampling and characterized by scanning mobility particle sizing (SMPS). Samples were extracted along the centerline at different heights above the burner (HAB) above the visible flame tip (>7 cm), and quenching experiments were performed to extract the aerosol samples at different dilution rates. Thereby, it was demonstrated that performing detailed quenching experiments is crucial for obtaining representative HIAT-SMPS data. In particular, agglomerates/aggregate sizes were overestimated by up to ~70 % if samples were not sufficiently diluted. If sufficient dilution was applied, distribution widths and mean particle mobility diameters were determined with high accuracy (sample standard derivation <5 %). Our data suggested the evolution of primary particle sizes was mostly completed <7 cm HAB and it was shown aggregates/agglomerates present above the visible flame were compact in structure (non- fractal). The mean diameter of the particle ensemble grew along the centerline from 6.9 nm (7 cm) to 11.4 nm (15 cm), while distribution widths grew from 1.42 to 1.52.
Keywords: Flame Spray Pyrolysis; SpraySyn2; Spray flame synthesis; Maghemite nanoparticles; Gas to particle-conversion; Hole in a tube sampling

Stickstoff basierte Flammschutzmittel für das Lasersintern: Optimierung und Analyse der Recyclingfähigkeit (Studienarbeit) - Hücker, Lars

Phosphorhaltige Lasersinter-Materialien mit Flammschutzwirkung: Optimierung und Analyse der Recyclingfähigkeit (Studienarbeit) - Schulz, Maurice

Einfluss von Temperatur und Strömungsführung auf die NH3-SCO sowie die NH3-SCR mit Partikeln aus einer Sprayflammensynthese - Bablitzka, Nico Janosch; Beimdiek, Janis

Evaluation of Surrogate Aerosol Experiments to Predict Spreading and Removal of Virus-Laden Aerosols - Beimdiek, Janis; Schmid, Hans-Joachim (Atmosphere)
Estimating the infection risks in indoor environments comprises the assessment of the behavior of virus-laden aerosols, i.e. spreading, mixing, removal by air purifiers etc. A promising experimental approach is based on using non-hazardous surrogate aerosols of similar size, e.g. salt particles, to mimic the virus aerosol behavior. This manuscript addresses the issue how a successful transfer of such experiments can be accomplished. Corresponding experiments in two very different environments, a large community hall and a seminar room, with optional use of air purifiers in various constellations were conducted. While high particle concentrations are advantageous in terms of avoiding influence of background aerosol concentrations, it is shown that appropriate consideration of aggregation and settling are vital to theoretically describe the experimentally determined course of particle concentrations. A corresponding model equation for a well-mixed situation is derived and the required parameters are thoroughly determined in separate experiments independently. It is demonstrated that clean air delivery rates (CADR) of air purifiers determined with this approach may differ substantially from common approaches not explicitly taking into account aggregation.
Keywords: surrogate aerosols; indoor air cleaners; ultra-fine particles; COVID-19; test method; field experiments: clean air delivery rate

Herstellung und Charakterisierung von Wood-Plastic-Composites (WPC) mit einer Matrix aus thermoplastischen Polyurethanen zur Erzeugung einer Holz-WPC-Verbundstruktur - Richters, Maximilian

An alternative and robust formulation of the fatigue crack growth rate curve for long cracks - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta (Engineering Fracture Mechanics)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Single-step self-punching lockbolt process for aluminum sheets without pre-hole - Han, Daxin; Kappe, Fabian; Vorderbrüggen, Julian; Jendrny, Jörg; Gorr, Eugen; Meschut, Gerson (Journal of Manufacturing Processes)
Keywords: Industrial and Manufacturing Engineering; Management Science and Operations Research; Strategy and Management

Methodenentwicklung zur rechnerischen Auslegung geklebter Stahlverbindungen unter Alterungsbeanspruchung im Stahl- und Anlagenbau - Beule, Felix; Sander, Sascha; Meschut, Gerson; Damm, Jannis; Kasper, Yann; Albiez, Matthias; Kötz, Fabian; Matzenmiller, Anton (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Klebstoffmodell - Parameteridentifikation, Verifikation und Validierung für den Lastfall Crash - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson (DECHEMA-Workshop für Klebstoffanwender: Simulation von Klebverbindungen)

Methodenentwicklung zur Simulation von hyperelastischen Klebverbindungen unter Crashbelastung - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson; Schmelzle, Lars; Possart, Gunnar; Mergheim, Julia; Steinmann, Paul

Experimental investigations of uniaxial and biaxial cold stretching within PC‐films and bars using optical measurements - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Abstract Polycarbonate (PC) is an amorphous polymer that is an extremely robust material with a high tenacity, and thus suitable for a lightweight construction with glass‐like transparency. Due to these advantageous properties, PC is often used in industry for example in medical devices, automotive headlamps, sporting equipment, electronics, and a variety of other products. PC is often subjected to uniaxial and biaxial loading conditions. Therefore, reliable material models have to take into account the various resulting experimental effects. For those reasons, we investigate PC specimens under uniaxial and biaxial loading by using different stretch rates and loading scenarios. In addition to that, we propose methods for optical measurement of local stretches to obtain the approximated local true stress. In future work, the displacement fields and the resulting reaction forces will be used for parameter identification of constitutive equations.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Multiscale simulation of polymer curing of composites combined mean-field homogenisation methods at large strains - Lenz, Peter; Mahnken, Rolf (International Journal of Solids and Structures)
Keywords: Applied Mathematics; Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science; Modeling and Simulation

Lebensdauerprognose für Stahlklebverbindungen bei multiaxialer Belastung mit Phasenverschiebung, veränderlicher Mittelspannung und variablen Amplituden - Carillo Beber, Vinicius; Fernandes, Pedro; Nagel, Christof; Köster, Christian; Matzenmiller, Anton; Hecht, Mathias; Baumgartner, Jörg; Melz, Tobias; Tews, Karina; Çavdar, Serkan; Meschut, Gerson (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Bruchmechanisches Schnittebenenkonzept zur lebensdauergerechten Auslegung von hyperelastischen Klebverbindungen bei multiaxialen und variablen Belastungsamplituden - Tews, Karina; Teutenberg, Dominik; Meschut, Gerson; Buczek, Moritz; Duffe, Tobias; Kullmer, Gunter (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Mechanisches Verhalten: Charakterisierung von Klebstoffen - Tews, Karina; Teutenberg, Dominik; Meschut, Gerson

„4 THe BoYZ“ – Widmungen im Szene-Graffiti aus konstruktionsgrammatischer Perspektive. Die multimodale Relator-Konstruktion als grammatische Musterbildung im Horizont des Textes - Tophinke, Doris; Dübbert, Alexander (Konstruktionsgrammatik X. Textsorten und Textmuster als Konstruktionen?)

Perspectives of children and young people on their education as preparing for their future in the digital age: In-depth qualitative study in five European countries. - Eickelmann, Birgit; Barbovschi, M.; Holmarsdottir, H.B.; Parsanoglou, D.; Sisask, M.; Labusch, Amelie (Understanding the everyday digital lives of children and young people)

Evaluation of Surrogate Aerosol Experiments to Predict Spreading and Removal of Virus-Laden Aerosols - Beimdiek, Janis; Schmid, Hans-Joachim (Atmosphere)
Keywords: surrogate aerosols; indoor air cleaners; ultra-fine particles; COVID-19; test method; field experiments: clean air delivery rate

Konzeptentwicklung für ein Stahlbatteriegehäuse unter besonderer Berücksichtigung der Fügetechnik und des Korrosionsschutzes - Chudalla, Nick; Schmolke, Tobias; Meschut, Gerson; Spohr, Sebastian; Eckstein, Lutz; Brunner-Schwer, Christian; Rethmeier, Michael; Nothelfer-Richter, Rolf; Hilt, MIchael (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Experimental and Theoretical Investigation of CO2 Absorption in Aqueous Solution of Glucosamine: Material Property and Equilibrium Data - Hami Dindar, Iman; Mirzaei, Mona; Baumhögger, Elmar; Lutters, Nicole; Kenig, Eugeny Y. (Journal of Chemical & Engineering Data)
Keywords: General Chemical Engineering; General Chemistry

Dynamics of an Absorption/Desorption Plant: Experimental Study and Model Validation - Weber, Mike; Lutters, Nicole; Kenig, Eugeny Y. (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Untersuchung des Füllverhaltens holzfaserverstärkter Kunststoffe (WPC) mit hohen Füllstoffgehalten - Flachmann, Felix

Methodenentwicklung zur Simulation des Viscous Fingering in Klebverbindungen von stahlintensiven Mischbaustrukturen - Al Trjman, Mohamad; Meschut, Gerson; Salten, Alexander Heinrich Johannes; Kenig, Eugeny Y.

A multi-step framework for the design of a flexible power-to-methane process - Bruns, Bastian; Gross, Michel; Grünewald, Marcus; Bertsch, Valentin; Riese, Julia (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Decentralized production concepts for bio-based polymers - implications for supply chains, costs, and the carbon footprint - Riese, Julia; Fasel, Henrik; Pannok, Maik; Lier, Stefan (Sustainable Production and Consumption)
Keywords: Industrial and Manufacturing Engineering; Renewable Energy; Sustainability and the Environment; Environmental Chemistry; Environmental Engineering

Experimentelle und numerische Analyse des Fließverhaltens von hochviskosen Wärmeleitstoffen im Fertigungsprozess - Gröger, Benjamin; Wiebicke, Felix; Koch, Ilja; Gude, Maik; Gilich, Julian; Meschut, Gerson (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Der Einfluss von Mikrostrukturen auf die Flüssigkeitsausbreitung in strukturierten Packungen - Dechert, Christopher; Kenig, Eugeny

Simulationsgestützte Bestimmung und Optimierung der Mischgüte in der Einschneckenextrusion - Frank, Maximilian

Wässrige Glucosaminlösung als neues Lösungsmittel zur CO2-Abscheidung - Hami Dindar, Iman; Lutters, Nicole; Kenig, Eugeny Y.

Diagnostics of Piezoelectric Bending Actuators Subjected to Varying Operating Conditions - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Hemsel, Tobias; Sextro, Walter (Electronics)
In applications of piezoelectric actuators and sensors, the dependability and particularly the reliability throughout their lifetime are vital to manufacturers and end-users and are enabled through condition-monitoring approaches. Existing approaches often utilize impedance measurements over a range of frequencies or velocity measurements and require additional equipment or sensors, such as a laser Doppler vibrometer. Furthermore, the non-negligible effects of varying operating conditions are often unconsidered. To minimize the need for additional sensors while maintaining the dependability of piezoelectric bending actuators irrespective of varying operating conditions, an online diagnostics approach is proposed. To this end, time- and frequency-domain features are extracted from monitored current signals to reflect hairline crack development in bending actuators. For validation of applicability, the presented analysis method was evaluated on piezoelectric bending actuators subjected to accelerated lifetime tests at varying voltage amplitudes and under external damping conditions. In the presence of a crack and due to a diminished stiffness, the resonance frequency decreases and the root-mean-square amplitude of the current signal simultaneously abruptly drops during the lifetime tests. Furthermore, the piezoelectric crack surfaces clapping is reflected in higher harmonics of the current signal. Thus, time-domain features and harmonics of the current signals are sufficient to diagnose hairline cracks in the actuators.
Keywords: piezoelectric transducer; self-sensing; fault detection; diagnostics; hairline crack; condition monitoring

Alexandra Treder (Universität Paderborn) rezensiert: Döll, Marion & Michalak, Magdalena (2023): Deutsch als Zweitsprache und inklusive Bildung. [Deutsch als Zweitsprache – Positionen, Perspektiven, Potenziale, Bd. 3]. Münster: Waxmann, 142 Seiten. ISBN 978-3-8309-4711-0. - Treder, Alexandra (Forschungsportal für Spracherwerb und Migration (daz-portal))

Modellbasierte Entwicklung von Ultraschallwandlern unter der Berücksichtigung von Nichtlinearitäten - Dymel, Collin
Ultraschallsysteme für das Herstellen für Bond- und Schweißverbindungen in der Halbleiterfertigung zeigen auf Grund des Betriebes unter hohen Anregungsniveaus nichtlineare Materialeigenschaften. Dabei wirken unterschiedliche Einflussfaktoren auf die elektrischen Eigenschaften und die mechanischen Übertragungscharakteristiken der Ultraschallsysteme ein. Die Herausforderungen ein solches geprägtes System auszulegen oder effizient und zuverlässig zu betreiben, sind aufgrund der Nichtlinearitäten relativ groß. Da für die Beschreibung der nichtlinearen Materialbeziehungen nur wenige Modelle und kaum quantitative Angaben vorliegen, werden die komplexen Wechselwirkungen von Materialparametern, Geometrie und Vorspannung des Schwingers, Betriebsgrößen (Strom, Spannung), Temperatur und Prozesslasten durch systematische Untersuchungen von Keramiken und Langevin-Schwingern messtechnisch erfasst. Aus den Messergebnissen werden einerseits eindimensionale Modelle für Voruntersuchungen als auch vollständige Materialparametersätze für die Simulation mittels dreidimensionaler FE-Modelle hergeleitet. Eine Methodik zur Ermittlung der Materialparameter und ein auf iterativen Simulationen von FE-Modellen basierendes Werkzeug zur Simulation der komplexen Wechselwirkungen werden vorgestellt. Anhand eines exemplarischen Ultraschallsystems wird gezeigt, dass die Wirkungen temperaturbedingter Vorspannungsverluste, Änderungen des elektrischen Klemmenverhaltens und Amplituden- und Frequenzänderungen während des Betriebes bei großen Amplituden und Prozesslasten durch die Variationen des Keramikvolumens und der Keramikposition positiv beeinflusst werden können.
Keywords: Nichtlineares piezoelektrisches Verhalten; Dehnungsabhängigkeit; Vorspannungseinfluss; Temperatureinfluss; Lasteinfluss; Langevin-Schwinger; Ultraschallwandler; Ultraschallbonden; FEM-Modell; Ultraschallschweißen; BVD-Modell

Influences of Weld Nugget Shape and Material Gradient on the Shear Strength of Resistance Spot‐Welded Joints - Schuster, Lilia; Olfert, Viktoria; Sherepenko, Oleksii; Fehrenbach, Clemens; Song, Shiyuan; Hein, David; Meschut, Gerson; Biro, Elliot; Münstermann, Sebastian (steel research international)
Resistance spot‐welded joints containing press‐hardened steels are seen to exhibit a fracture mode called total dome failure, where the weld nugget completely separates from one steel sheet along the weld nugget edge. The effect of weld nugget shape and material property gradients is studied based on damage mechanics modeling and experimental validation to shed light on the underlying influencing factors. For a three‐steel‐sheet spot‐welded joint combining DP600 (1.5 mm)–CR1900T (1.0 mm)–CR1900T (1.0 mm), experiments under shear loading reveal that fracture occurs in the DP600 sheet along the weld nugget edge. In subsequent numerical simulation studies with damage mechanics models whose parameters are independently calibrated for every involved material configuration, three variations of the geometrical joint configuration are considered—an approximation of the real joint, one variation with a steeper weld nugget shape, and one variation with a less pronounced gradient between weld nugget material and heat‐affected zone material properties. The results of the finite‐element simulations show that a shallower weld nugget and a more pronounced material gradient lead to a faster increase of plastic strain at the edge of the weld nugget and promote the occurrence of total dome failure.
Keywords: Materials Chemistry; Metals and Alloys; Physical and Theoretical Chemistry; Condensed Matter Physics

Zur Abscheidung von Tröpfchen-Aerosolen in filternden Abscheidern - Hassel, Richard

Untersuchung des Lösungsmitellseinflusses auf die Synthese von Manganoxid-Nanopartikeln in der Flammenspraypyrolyse - Zink, Timm Florian

Construction of A-stable explicit last-stage diagonal implicit Runge–Kutta (ELDIRK) methods - Mahnken, Rolf; Westermann, Hendrik (Computational Mechanics)
ELDIRK methods are defined to have an Explicit Last stage in the general Butcher array of Diagonal Implicit Runge-Kutta methods, with the consequence, that no additional system of equations must be solved, compared to the embedded RK method. Two general formulations for second- and third-order ELDIRK methods have been obtained recently in Mahnken [21] with specific schemes, e.g. for the embedded implicit Euler method, the embedded trapezoidal-rule and the embedded Ellsiepen method. In the first part of this paper, we investigate some general stability characteristics of ELDIRK methods, and it will be shown that the above specific RK schemes are not A-stable. Therefore, in the second part, the above-mentioned general formulations are used for further stability investigations, with the aim to construct new second- and third-order ELDIRK methods which simultaneously are A-stable. Two numerical examples are concerned with the curing for a thermosetting material and phase-field RVE modeling for crystallinity and orientation. The numerical results confirm the theoretical results on convergence order and stability.
Keywords: Applied Mathematics; Computational Mathematics; Computational Theory and Mathematics; Mechanical Engineering; Ocean Engineering; Computational Mechanics

Children and young people’s ICT experiences in school education: Participatory research design to engage children and young people as experts in research - Labusch, Amelie; Eickelmann, Birgit; Casamassima, Gianna; Drossel, Kerstin; Gudmundsdottir, G.B.; Kazani, A.; Mifsud, L.; Symeonaki, M.; Teidla-Kunitsõn, G. (Understanding the everyday digital lives of children and young people)

Anisotropic Mechanical and Microstructural Properties of a Ti-6Al-7Nb Alloy for Biomedical Applications Manufactured via Laser Powder Bed Fusion - Milaege, Dennis; Eschemann, Niklas; Hoyer, Kay-Peter; Schaper, Mirko (Crystals)
Through tailoring the geometry and design of biomaterials, additive manufacturing is revolutionizing the production of metallic patient-specific implants, e.g., the Ti-6Al-7Nb alloy. Unfortunately, studies investigating this alloy showed that additively produced samples exhibit anisotropic microstructures. This anisotropy compromises the mechanical properties and complicates the loading state in the implant. Moreover, the minimum requirements as specified per designated standards such as ISO 5832-11 are not met. The remedy to this problem is performing a conventional heat treatment. As this route requires energy, infrastructure, labor, and expertise, which in turn mean time and money, many of the additive manufacturing benefits are negated. Thus, the goal of this work was to achieve better isotropy by applying only adapted additive manufacturing process parameters, specifically focusing on the build orientations. In this work, samples orientated in 90°, 45°, and 0° directions relative to the building platform were manufactured and tested. These tests included mechanical (tensile and fatigue tests) as well as microstructural analyses (SEM and EBSD). Subsequently, the results of these tests such as fractography were correlated with the acquired mechanical properties. These showed that 90°-aligned samples performed best under fatigue load and that all requirements specified by the standard regarding monotonic load were met.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Edge-Connectivity and Pairwise Disjoint Perfect Matchings in Regular Graphs - Ma, Yulai; Mattiolo, Davide; Steffen, Eckhard; Wolf, Isaak Hieronymus (Combinatorica)
For 0 ≤ t ≤ r let m(t, r) be the maximum number s such that every t-edge-connected r-graph has s pairwise disjoint perfect matchings. There are only a few values of m(t, r) known, for instance m(3, 3) = m(4, r) = 1, and m(t, r) ≤ r − 2 for all t = 5, and m(t, r) ≤ r − 3 if r is even. We prove that m(2l, r) ≤ 3l − 6 for every l ≥ 3 and r ≥ 2l.
Keywords: Computational Mathematics; Discrete Mathematics and Combinatorics

Vmin Testing under Variations: Defect vs. Fault Coverage - Jafarzadeh, Hanieh; Klemme, Florian; Amrouch, Hussam; Hellebrand, Sybille; Wunderlich, Hans-Joachim (IEEE Latin American Test Symposium (LATS), Maceió, Brazil, April 9-12, 2024)

Innovative measurement system for saber curvature observation in straightening processes - Bathelt, Lukas; Djakow, Eugen; Henke, Christian; Trächtler, Ansgar (Procedia Computer Science)
Keywords: General Engineering

LiDAR-Sensormodell basierend auf zeitabhängigem Photon Mapping - Bußemas, Leon; Fittkau, Niklas; Gausemeier, Sandra; Trächtler, Ansgar; Rüddenklau, Nico (VDI Mechatroniktagung Dresden 2024)

Herstellung und Charakterisierung von Wood-Plastic-Composites (WPC) mit einer Matrix aus thermoplastischen Polyurethanen zur Erzeugung einer Holz-WPC-Verbundstruktur - Richters, Maximilian

Ein Beitrag zur Erarbeitung von Fertigungsrichtlinien für das Kunststoff Freiformen - Hirsch, Andre

Materialschonende Verarbeitung von Thermoplasten auf Wave-Schnecken - Schall, Christoph Wilhelm Theodor

Experimentelle und simulative Analyse der Mischwirkung in Einschneckenextrudern - Schadomsky, Michael

Weiterentwicklung des Exponentialansatzes zur Beschreibung von Rissfortschrittskurven - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta

Klopstocks lyrisches Spätwerk. Perspektivwechsel und Blickerweiterungen - Elit, Stefan („Wer wird nicht einen Klopstock loben?“ Friedrich Gottlieb Klopstocks poetische Innovationen und ihre produktive Rezeption)

Digitale Plattformen im industriellen Mittelstand

Digitale Plattformen im industriellen Mittelstand

Evaluation of the Influence of Particle Type, Shape and Size on the Thermal Conductivity of Filled Polymers in the Fused Filament Fabrication Process - Moritzer, Elmar; Elsner, Christian Lennart
The Fused Filament Fabrication (FFF) process is increasingly used for the manufacturing of individualized and complex structures, which continuously results in new requirements regarding the material properties. A characteristic material property for polymers is the low thermal conductivity. However, for specific applications, such as additively manufactured injection molding tool inserts, increased thermal conductivity is advantageous. In this study, the influence of fillers of different types, shapes and sizes on the resulting thermal conductivity of compounds is investigated. The aim is to analyze the effects of the fillers, considering the FFF-typical strand structure. The first step is to characterize the fillers in terms of shape and size. Based on this, the resulting thermal conductivity of specimens manufactured in the FFF process for different build orientations is specifically examined and compared to injection molding. This ensures that the process- and material-related anisotropy of the specimens is considered in the analysis. For the evaluation, a methodology is developed to be applied in Laser Flash Analysis (LFA), which allows the results to be evaluated despite the characteristic FFF surface structure. For the final visualization of the influence of the particle size on the particle orientation, Scanning Electron Microscopy (SEM) images of the relevant polymer compounds are made. The investigations provide a data basis regarding the influence of the particle type, shape and size on the thermal conductivity as well as for the requirement-oriented selection of fillers for processing thermally conductive polymer compounds in the FFF process.

Modular 3D roller straightening – A new approach to straightening and forming of spring steel wires (X10CrNi18-8) - Dahms, Frederik Simon; Homberg, Werner (Materials Research Proceedings)
Abstract. Spring steel wires are usually supplied and stored on coils. The manufacturing and coiling processes of these wires induce inhomogeneous plastic deformations that lead to undesirable residual stresses and varying wire curvatures in the semi-finished product. These residual stresses and curvatures defects are causing varying process conditions in the subsequent manufacturing processes, which have a negative impact on the product quality, leading to wastage and thus affecting the economic and ecological efficiency. Especially the curvature deviations must be compensated for the stability of the subsequent processes. This is usually realised with roller straighteners, which are set manually by the machine operators only at the beginning of a process. In this paper, we introduce a new approach with a modular straightening-machine design and a new set-up process. The more isolated deformation behaviour in a module-based straightener overcomes the complexity of interactions between the close-positioned spaced straightening rollers. This is combined with a set-up process that is independent of conventional material testing, modelling the actual and batch-specific behaviour of the wire in the straightening process. The exact knowledge and time-consuming determination of the material properties thus becomes obsolete. The experimental investigations show the influence of defined straightening strategies on the residual stress evolution and the residual forming limit of the spring steel wires (X10CrNi18-8) in the new straightening process.

Evaluating Security Through Isolation and Defense in Depth - Bodden, Eric; Pottebaum, Jens; Fockel, Markus; Gräßler, Iris (IEEE Security & Privacy)
Keywords: Law; Electrical and Electronic Engineering; Computer Networks and Communications

“Der Draht ist gut, hält uns ab vom dummen Leben“. Ironisierung als kommunikativer Versuch des Umgangs mit Entwertungs- und Gewalterfahrungen durch jüdische Textproduzenten im Getto Litzmannstadt - Markewitz, Friedrich (Invective Discourse)
Immediately after the National Socialist seizure of power, a comprehen-sive social, legal and ultimately existential exclusion of Jewish people began. The disturbing perception of the break-up of previous understandings of the world was intensified against the background of the acts of annihilation by the National Socialists. Countering this in a communicative form became an often agonizing challenge for Jewish speakers, but also a necessary need. This paper will focus on a communicative phenomenon that has been little researched in linguistics so far: The use of irony to counter experiences of devaluation and violence. By eval-uating ironic utterances in textual communications of the Litzmannstadt ghetto, the criticism of elements of National Socialist ideology will be tentatively made understandable, as well as the experiences of violence within the ghetto.

Haus oder Schule? oder Haus und Schule? Zur kulturell-gesellschaftlichen Bedeutung der historischen Textsorte 'Schulprogramm' hinsichtlich der Konstitution, Festigung wie Abgrenzung des Erziehungssystems im 19. Jahrhundert - Markewitz, Friedrich (Textsorten in Sprach-, Kultur- und Sozialgeschichte)

Ironie - Markewitz, Friedrich
Ironie lässt sich als uneigentliches Kommunikationsmittel beschreiben, mit dem etwas anderes zum Ausdruck gebracht wird, als Sprecher*innen oder Schreiber*innen eigentlich meinen. Dies erfordert eine Differenzierung in Gesagtes und Gemeintes. Doch diese Differenzierung ist längst nicht immer eindeutig und so lebt Ironie von einer interpretatorischen Ambivalenz, ob eine Äußerung wörtlich oder ironisch zu verstehen ist. Aufgrund dieser Ambivalenz und ihrer kulturgeschichtlichen Entwicklung erscheint Ironie als ebenso faszinierendes wie komplexes Sprach-Phänomen. Die vorliegende Einführung gibt aus kulturlinguistischer Perspektive Einblicke in die verschiedenen Möglichkeiten der theoretischen Beschreibung, methodischen Erfassung sowie empirischen Analyse von Ironie. Dabei werden einerseits alltagssprachliche Formen ironischen Kommunizierens in den Blick genommen, andererseits Möglichkeiten des interdisziplinären Anschlusses, um Ironie als linguistisches sowie als kulturgeschichtliches Phänomen zugänglich zu machen.

Method development (modelling, simulation, characterisation) in adhesive bonding technology - Beule, Felix; Al Trjman, Mohamad; Teutenberg, Dominik; Meschut, Gerson

Experimentelle und numerische Analyse des Fließverhaltens von hochviskosen Wärmeleitstoffen im Fertigungsprozess - Gilich, Julian; Meschut, Gerson; Gröger, Benjamin; Wiebicke, Felix; Koch, Ilja; Gude, Maik (14. Doktorandenseminar Klebtechnik)

A large deformation gradient theory for glassy polymers by means of micromorphic regularization - Hamdoun, Ayoub; Mahnken, Rolf (Archive of Applied Mechanics)
Abstract Cold forming of polycarbonate films results in the formation of shear bands in the necking zone. The numerical results obtained from standard viscoplastic material models exhibit mesh size dependency, requiring mathematical regularization. For this purpose, we present in this work a large deformation gradient theory for a viscoplastic isotropic material model published before. We extend our model to a micromorphic model by introducing a new micromorphic variable as an additional degree of freedom along with its first gradient. This variable represents a microequivalent plastic strain. The relation between the macroequivalent plastic strain and the micromorphic variable is accomplished by a micromorphic coupling modulus. This coupling forces proximity between the macro- and microvariables, leading to the targeted regularization effect. The micromorphic model is implemented as a three-dimensional initial boundary value problem in an in-house finite element tool. The analysis is performed for both uniaxial and biaxial specimens. The provided numerical examples show the ability of our model to regularize shear bands within the specimens and address the issue of localization.

Digitale Plattformen im industriellen Mittelstand

Uniaxial and biaxial experimental investigation of glassy polymers - Hamdoun, Ayoub; Mahnken, Rolf (Polymer)

Einfluss von Luftfeuchtigkeit auf die Fließfähigkeit von Polymerpulvern für das selektive Lasersintern (Studienarbeit) - Walljasper, Ben

Entwicklung eines Bildanalyseverfahrens zur Erfassung des dynamischen Fließverhaltens von Schüttgütern - Liu, Diyi

Mechanically Joined Extrusion Profiles for Battery Trays - Neumann, Stefan; Meschut, Gerson; Otroshi, Mortaza; Kneuper, Florian; Schulze, Andre; Tekkaya, Erman

Experimentelle und modellbasierte Untersuchungen zum Prozessverhalten von teilkristallinen Materialien im Spritzgießsonderverfahren GITBlow - Kröker, Michael

Die Schrift entHeiligen. Praktisch-theologische Überlegungen zum Bibelgebrauch als Transformation des Heiligen - Schroeter-Wittke, Harald (Heilige Schriften in der Kritik. XVII. Europäischer Kongress für Theologie (5.-8. September 2021 in Zürich). VWGTh 68)

Predicting the Bond Quality of Heavy Copper Wire Bonds using a Friction Model Approach - Althoff, Simon
Ultraschall-Drahtbonden ist eine Standardtechnologie im Bereich der Aufbau- und Verbindungstechnik von Leistungshalbleitermodulen. Um Prozessschritte und damit wertvolle Zeit zu sparen, sollen die Kupferdickdrähte für die Leistungshalbleiter auch für die Kontaktierung von eingespritzten Anschlusssteckern im Modulrahmen verwendet werden. Das Kontaktierungsverfahren mit diesen Drähten auf Steckern in dünnwandigen Kunststoffrahmen führt häufig zu unzureichender Bondqualität. In dieser Arbeit wird das Bonden von Anschlusssteckern experimentell und anhand von Simulationen untersucht, um die Prozessstabilität zu steigern. Zunächst wurden Experimente auf Untergründen mit hoher Steifigkeit durchgeführt, um Störgrößen von Untergrundeigenschaften zu verringern. Die gewonnenen Erkenntnisse erlaubten die Entwicklung eines Simulationsmodells für die Vorhersage der Bondqualität. Dieses basiert auf einer flächenaufgelösten Reibarbeitsbestimmung im Fügebereich unter Berücksichtigung des Ultraschallerweichungseffektes und der hierdurch entstehenden hohen Drahtverformung. Experimente an den Anschlusssteckern im Modulrahmen zeigten eine verringerte Relativverschiebung zwischen Draht und Stecker, was zu einer deutlichen Verringerung der Reibarbeit führt. Außerdem wurden verminderte Schwingamplituden des Bondwerkzeugs nachgewiesen. Dies führt zu einer weiteren Reduktion der Reibarbeit. Beide Effekte wurden mithilfe eines Mehrmassenschwingers modelliert. Die gewonnenen Erkenntnisse und die erstellten Simulationsmodelle ermöglichen die Entwicklung von Klemmvorrichtungen, welche die identifizierten Störgrößen gezielt kompensieren und so ein verlässliches Bonden der Anschlussstecker im gleichen Prozessschritt ermöglichen, in dem auch die Leistungshalbleiter kontaktiert werden.
Keywords: heavy copper bonding; wire bonding; quality prediction; friction model; point-contact-element

Modellierung und Optimierung reibungsbasierter Ultraschall-Pulvertransportprozesse - Dunst, Paul
Der Transport feiner Pulver mit in der Regel sehr hohen adhäsiven und kohäsiven Eigenschaften stellt für viele konventionelle Transportsysteme eine große Herausforderung dar. Durch die Anwendung von Ultraschallschwingungen können insbesondere die hohen adhäsiven Kontaktkräfte und damit auch die Reibungseigenschaften manipuliert werden. Ein neu entwickeltes Pulvertransportsystem nutzt Ultraschallschwingungen, um die effektiven Tangentialkräfte im Pulver-Rohrkontakt zu reduzieren. Durch den koordinierten Einsatz von Ultraschallpulsen während einer niederfrequenten harmonischen Axialschwingung des Transportrohres wird ein kontinuierlicher Pulvertransport ermöglicht. Nach einer Einführung in die Grundlagen der Reibung und Reibungsmanipulation von Festkörpern und Pulvern sowie der Charakterisierung von Pulvern wird das Pulvertransportsystem auf Basis der Reibungsmanipulation inklusive der Leistungselektronik und der Ansteuerungshardware vorgestellt. Eine Sensitivitätsanalyse zeigt, dass die Anregungsparameter des Pulvertransportsystems ein großes Optimierungspotential aufweisen. Es wird ein effizientes, modulares Modell des Pulvertransportsystems vorgestellt, welches neben dem eigentlichen Modell des Transportprozesses ein Modell der Rohrschwingung und ein kennlinienbasiertes Modell des Pulver-Rohrkontakts beinhaltet. Mithilfe des Modells des Pulvertransportsystems werden Anregungsparameter hinsichtlich Amplituden und Frequenzen der auftretenden Schwingungen sowie der Schaltzeiten des Ultraschallpulses optimiert.
Keywords: Ultraschall; Pulvertransport; Modellierung; Optimierung; Reibung; Adhäsion; Kohäsion; Reibungsmanipulation

Hardware-in-the-Loop-Simulation von HD-Scheinwerfer-Steuergeräten zur Entwicklung von Lichtfunktionen in virtuellen Nachtfahrten - Rüddenklau, Nico

Entwurf und Analyse modellprädiktiver Regelungsansätze zur Steigerung des Immersionsempfindens in interaktiven Fahrsimulationen - Biemelt, Patrick

Development of a numerical simulation model for self-piercing riveting of additive manufactured AlSi10Mg - Heyser, Per; Petker, Rudolf; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Laser additive manufacturing processes are used for the production of highly complex geometric structures due to their high geometric freedom. Additive manufacturing processes, in particular powder-based selective laser melting, are used to produce metallic additive manufactured components for the automotive and aerospace industries. Different materials are often joined together to realize sustainable lightweight construction. The production of such mixed construction joints is often realized using mechanical joining technology (e.g. self-piercing riveting). However, there is currently very little experience with the mechanical joining of metallic additive manufacturing components. Furthermore, there is insufficient knowledge about the effects that occur during the mechanical joining of additive manufacturing components. In this article, a method is presented to investigate the joinability of additively manufactured components with conventionally manufactured components using a numerical simulation of the self-piercing riveting process. For this purpose, the additive manufacturing materials are characterized experimentally, the simulation model is configured, and the joining process with additive manufacturing materials is represented in the numerical simulation. Furthermore, the influence of the building direction on the mechanical properties is shown using miniature tensile specimens. Besides the configuration of the simulation model, the influence of heat treatment on the self-piercing riveting process is presented.
Keywords: Mechanical Engineering; General Materials Science

Systematisierung einer rechnergestützten Auswertemethode zur Versagensanalyse geklebter Verbindungen - Chudalla, Nick; Meschut, Gerson; Schneider, Miriam; Smart, Dominic

Konzeptentwicklung für ein Stahlbatteriegehäuse unter besonderer Berücksichtigung der Fügetechnik und des Korrosionsschutzes - Schmolke, Tobias; Meschut, Gerson; Spohr, Sebastian; Eckstein, Lutz; Brunner-Schwer, Christian; Rethmeier, Michael; Nothhelfer-Richter, Rolf; Hilt, Michael

Der Tod und die Liebe: Die Metaphysik der Kommunikation - Fuchs, Christian (Soziale Ordnungen des Sterbens: Theorie, Methodik und Einblicke in die Vergänglichkeit)

Lebensdauerprognose für Stahlklebverbindungen bei multiaxialer Belastung mit Phasenverschiebung, veränderlicher Mittelspannung und variablen Amplituden - Nagel, Christof; Carillo Beber, Vinicius; Mayer, Bernd; Köster, Christian; Matzenmiller, Anton; Hecht, Matthias; Baumgartner, Jörg; Melz, Tobias; Tews, Karina; Çavdar, Serkan; Meschut, Gerson (23. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Experimental investigation of the fatigue behavior and calculation of the service life of adhesively bonded joints - Tews, Karina; Teutenberg, Dominik; Meschut, Gerson

Experimental and numerical investigation of the damping properties of adhesively bonded tubular steel joints - Göddecke, Johannes; Meschut, Gerson; Damm, Jannis; Albiez, Matthias; Ummenhofer, Thomas; Kötz, Fabian; Matzenmiller, Anton (The Journal of Adhesion)

Experimental Investigations of Carbon Fiber Reinforced Polymer Composites and Their Constituents to Determine Their Elastic Material Properties and Complementary Inhomogeneous Experiments with Local Strain Considerations - Penner, Eduard; Caylak, Ismail; Mahnken, Rolf (Fibers and Polymers)
Abstract Composite materials, such as fiber reinforced polymers, become increasingly important due to their excellent mechanical and lightweight properties. In this respect, this paper reports the characterization of a unidirectional carbon fiber reinforced polymer composite material. Particularly, the mechanical behavior of the overall composite and of the individual constituents of the composite is investigated. To this end, tensile and shear tests are performed for the composite. As a result, statistics for five transversely isotropic material parameters can be established for the composite. For the description of the mechanical properties of the constituents, tensile tests for the carbon fiber as well as for the polymer matrix are carried out. In addition, the volume fraction of fibers in the matrix is determined experimentally using an ashing technique and Archimedes’ principle. For the Young’s modulus of the fiber, the Young’s modulus and transverse contraction of the matrix, as well as the volume fraction of the constituents, statistics can be concluded. The resulting mechanical properties on both scales are useful for the application and validation of different material models and homogenization methods. Finally, in order to validate the obtained properties in the future, inhomogeneous tests were performed, once a flat plate with a hole and a flat plate with semicircular notches.
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Non-local integral-type damage combined to mean-field homogenization methods for composites and its parallel implementation - Lenz, Peter; Mahnken, Rolf (Composite Structures)
Keywords: Civil and Structural Engineering; Ceramics and Composites

Integrating Prospective Scenarios in Life Cycle Engineering: Case Study of Lightweight Structures - Ostermann, Moritz; Grenz, Julian; Triebus, Marcel; Cerdas, Felipe; Marten, Thorsten; Tröster, Thomas; Herrmann, Christoph (Energies)
Lightweight design is a common approach to reduce energy demand in the use stage of vehicles. The production of lightweight materials is usually associated with an increase in energy demand, so the environmental impacts of lightweight structures need to be assessed holistically using a life cycle assessment. To estimate the life cycle environmental impacts of a product in its developmental stage, for example, by life cycle engineering, future changes in relevant influencing factors must be considered. Prospective life cycle assessment provides methods for integrating future scenarios into life cycle assessment studies. However, approaches for integrating prospective life cycle assessment into product development are limited. The objective of this work is to provide the methodological foundation for integrating future scenarios of relevant influencing factors in the development of lightweight structures. The applicability of the novel methodology is demonstrated by a case study of a structural component in a steel, aluminium, and hybrid design. The results show that appropriate decarbonisation measures can reduce the life cycle greenhouse gas emissions by up to 95 percent until 2050. We also found that shifts in the environmentally optimal design are possible in future scenarios. Therefore, the methodology and data provided contribute to improved decision-making in product development.
Keywords: Life Cycle Engineering; Life Cycle Assessment; Lightweight Design; Prospective LCA; Future-oriented LCA; Energy System; Material production; Sustainable production

KrafT: Bildungsdokumentation in der inklusiven Schule partizipativ gestalten. 9. Paderborner Grundschultag zum Thema: „Demokratie Lernen von Anfang an“. Online - Büker, Petra; Herding, Jana; Drexler, Leonie

Automatisierung der Auswertung rheologischer Messungen (Studienarbeit) - Gunasagran, Sharin Kumar; Neukötter, Moritz

Instabilities of Polymer Melt Suspensions under Uniaxial Extension (Poster) - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Experimentelle und numerische Untersuchung des Einflusses variabler Betriebstemperaturen auf das Trag- und Versagensverhalten struktureller Klebverbindungen unter Crashbelastung - Schmelzle, Lars; Mergheim, Julia; Possart, Gunnar; Striewe, Marius; Meschut, Gerson (23. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Analysis of temperature effect on strength and microstructure in friction induced recycling process (FIRP) - Borgert, Thomas; Homberg, Werner (Materials Research Proceedings)
Abstract. In order to reduce global energy consumption in production and industry along with the associated CO2 emissions, existing resources must be used more efficiently. This includes the energy-efficient and comprehensive recycling of a wide range of metals. Especially for the production of aluminium, there is a large potential for saving energy using efficient recycling processes. With regard to the recycling of aluminium studies have shown that solid-state recycling processes are significantly more efficient considering the used energy and resources compared to the conventional, smelting-metallurgical recycling process. In this paper, the direct and energy-efficient friction-induced recycling process (FIRP) based on the conform process is further described and analysed in terms of the temperature-property relationships. For this purpose, the influence of the processing temperature on the microstructure and properties of the recycled semi-finished products is investigated using the toll system that enables an ECAP forming. Specific sections of the (in theory) infinite, recycled semi-finished product are taken and analysed at different process temperatures of the solid state recycling process. Based on these sections, the properties in terms of mechanical hardness, strength, ductility and grain size are analysed and a degressive relationship between process temperature and mechanical hardness up to a temperature of 270 °C can be shown. Applying the Hall-Petch relationship, it is analysed whether there is a correlation between the strength and the microstructure in the form of the grain size.
Keywords: Recycling; Aluminium; Friction-Induced; Energy Efficiency

Untersuchung überlagerter Effekte von Druckverlust und Totvolumen durch Rekuperation am isobaren Expansionsmotor - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny Y. (Chemie Ingenieur Technik)
Die Wirtschaftlichkeit von Wärmemotoren wird maßgeblich durch die Rückführung von Wärme in Rekuperatoren beeinflusst. Beim isobaren Expansionsmotor vom Bush-Typ, einem Wärmemotor, welcher bereits mit Wärmequellen ab 60°C betrieben werden kann, steigt der thermische Wirkungsgrad durch den Einsatz von Rekuperatoren signifikant. Gleichzeitig wirken sich das Fluidvolumen des Wärmeübertragers sowie der beim Betrieb auftretende Druckverlust negativ auf den thermischen Wirkungsrad aus. In dieser Arbeit wird der Zusammenhang von Totvolumen, Druckverlust und Wärmerückgewinnung untersucht und Empfehlungen für den Betrieb von Rekuperatoren am isobaren Expansionsmotor gegeben.
Keywords: Isobarer Expansionsmotor; Dynamische Wärmeübertragungsmodellierung; Phasenwechsel; dichte Arbeitsmedien

Investigation of the leak tightness of structural adhesive joints for use in battery housings considering mechanical and corrosive loads - Schmolke, Tobias; Teutenberg, Dominik; Meschut, Gerson (The Journal of Adhesion)

Damping Properties of Bonded Structures Under Dynamic Loading - Göddecke, Johannes; Meschut, Gerson

Experimental and simulative determination and correction of the effective gap extension in structured coaxial measuring systems - Josch, Sebastian; Jesinghausen, Steffen; Dechert, Christopher; Schmid, Hans-Joachim (Rheologica Acta)
Abstract The use of structured measuring systems to prevent wall slip is a common approach to obtain absolute rheological values. Typically, only the minimum distance between the measuring surfaces is used for further calculation, implying that no flow occurs between the structural elements. But this assumption is misleading, and a gap correction is necessary. To determine the radius correction $$Δ r$$ Δ r for specific geometries, we conducted investigations on three Newtonian fluids (two silicon oils and one suspension considered to be Newtonian in the relevant shear rate range). The results show that $$Δ r$$ Δ r is not only shear- and material-independent, but geometry-dependent, providing a Newtonian flow behaviour in a similar viscosity range. Therefore, a correction value can be determined with only minute deviations in different Newtonian fluids. As the conducted laboratory measurements are very time-consuming and expensive, a CFD-approach with only very small deviations was additionally developed and compared for validation purposes. Therefore, simulation is an effective and resource-efficient alternative to the presented laboratory measurements to determine $$Δ r$$ Δ r for the correction of structured coaxial geometries even for non-Newtonian fluids in the future.
Keywords: rheology; rheometry; suspension; coaxial; correction

Bootstrapping the Open Science culture: The fellowship approach - Heck, Tamara; Steinhardt, Isabel; Rahal, Rima-Maria; Schubotz, Moritz; Scholl, Dominik; Behrens, Sarah (Research Ideas and Outcomes)
Keywords: Open Science

Correction: Thermal influence of resistance spot welding on a nearby overmolded thermoplastic–metal joint - Wippermann, Jan; Meschut, Gerson; Koshukow, Wikentij; Liebsch, Alexander; Gude, Maik; Minch, Steven; Kolbe, Björn (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Förderung der sozialen Partizipation von Kindern im inklusiven Unterricht. Workshop auf dem 9. Paderborner Grundschultag. Thema: „Demokratie von Anfang an! Demokratie in der Grundschule erfahren, mitgestalten und reflektieren“ - Görel, Gamze; Hellmich, Frank; Löper, Marwin Felix